The History and Deep Time of Climate Crisis - Power, Amanda (2022)
A question that is not widely asked, but perhaps should be, is: how responsible are historians for today’s threats to much of life on earth? What part has been played by western historical constructions of the human past, the sense of temporality and meaning on which it has been based, and the ethical imperatives it encodes? In what ways has the modern, professionalised discipline, with its roots in Judeo-Christian universalism and ideas of historical exceptionalism, together with European imperial, enlightenment, and nationalist projects, taken possession of deep time and used it to delegitimise other ways of thinking about humans and the planetary past? How can thinking with deep time help historians to undo westernised modernity’s tight grip on space and time, and craft approaches to the past that give urgently needed room to all life and non-life, relationships, and possibilities?
Keywords: Anthropocene; climate history; Environmental History; progress narratives; Medieval Theology; medieval governance; climate crisis; History; deep time